2015
DOI: 10.1152/ajpgi.00360.2012
|View full text |Cite
|
Sign up to set email alerts
|

The gastrointestinal microbiota and colorectal cancer

Abstract: The human gut is home to a complex and diverse microbiota that contributes to the overall homeostasis of the host. Increasingly, the intestinal microbiota is recognized as an important player in human illness such as colorectal cancer (CRC), inflammatory bowel diseases, and obesity. CRC in itself is one of the major causes of cancer mortality in the Western world. The mechanisms by which bacteria contribute to CRC are complex and not fully understood, but increasing evidence suggests a link between the intesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
130
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(135 citation statements)
references
References 192 publications
0
130
0
2
Order By: Relevance
“…These results correlate with our hypothesis that the specific tumor microenvironment could modulate the tumor microbiome resulting in the selection of similar taxa resistant to conditions of hypoxia, occurring due to the insufficient vascularization, low pH and depletion of glucose and other nutrients. 51,52 A number of research studies have analyzed the microbiome composition of tissue and fecal samples from CRC patients 41 and our study alineates in general with their findings. In our study, however, although we observed a lower phylogenetic diversity and richness in tumor tissues compared to adjacent tissues, Principal Coordinate Analysis of weighted and unweight Unifrac matrices and ANOSIM analysis showed no extensive differences in composition between adjacent and tumor microbial communities in both cohorts, which could be due in part to the fact that adjacent tissues, although non-tumoral, are in close proximity to tumors sharing the same intestinal microenvironment.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…These results correlate with our hypothesis that the specific tumor microenvironment could modulate the tumor microbiome resulting in the selection of similar taxa resistant to conditions of hypoxia, occurring due to the insufficient vascularization, low pH and depletion of glucose and other nutrients. 51,52 A number of research studies have analyzed the microbiome composition of tissue and fecal samples from CRC patients 41 and our study alineates in general with their findings. In our study, however, although we observed a lower phylogenetic diversity and richness in tumor tissues compared to adjacent tissues, Principal Coordinate Analysis of weighted and unweight Unifrac matrices and ANOSIM analysis showed no extensive differences in composition between adjacent and tumor microbial communities in both cohorts, which could be due in part to the fact that adjacent tissues, although non-tumoral, are in close proximity to tumors sharing the same intestinal microenvironment.…”
Section: Discussionmentioning
confidence: 55%
“…Studies have increasingly addressed the role of the gut microbiome in CRC since a dysbiotic state has been reported in the stools and tissue-adherent microbiome of adenoma and CRC patients (recently reviewed by Keku et al 41 ). Our study aimed to test the hypothesis that, regardless of the geographic origin, the tumor microenvironment could modulate the microbiota in situ generating compositional and functional similarities in the tumor microbiomes.…”
Section: Discussionmentioning
confidence: 99%
“…A biomarker is defined as an objectively measurable characteristic that is objectively measured and evaluated as an indicator of normal biologic or pathogenic processes, or pharmacological responses to a specified therapeutic intervention [1]- [3]. Ideally it should be measured from easily obtained bodily fluids and waste such as plasma, serum, urine and faecal matter for improved patient acceptance; if not feasible then invasive techniques such as tissue biopsy are acceptable.…”
Section: Introductionmentioning
confidence: 99%
“…The microbiome influences Phase I and Phase II drug metabolism (43) . In recent years, a number of studies have pointed to links between the gut microbiota and pathophysiology of diabetes (8,36), cancer (27), bowel disorders (9,15), liver disease (46), immune conditions (33), and the metabolic syndrome (12). Increased understanding of these processes may unravel tremendous potential for therapeutics.…”
mentioning
confidence: 99%